2018
DOI: 10.3892/ol.2018.8077
|View full text |Cite
|
Sign up to set email alerts
|

Musashi‑2 is a prognostic marker for the survival of patients with cervical cancer

Abstract: Cervical cancer is one of the most common gynecological malignancies. Mousasi 2 (Msi2) is a RNA-binding protein that regulates various key cellular functions and has emerged as a crucial regulator of cancer development. However, the clinical significance and biological functions of Msi2 in cervical cancer remain unknown. The current study assessed the expression of Msi2 mRNA using reverse transcription-quantitative polymerase chain reaction. Furthermore, the expression of Msi2 was examined in 162 cervical canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 22 publications
3
29
0
1
Order By: Relevance
“…Its role seems to be explicated in different processes, among which: epithelial-mesenchymal transition, migration, invasion, cell proliferation, and drug resistance [17]. While for many tumors, such as those arising from breast [18], cervical [9], colon [19], lung [6], etc. the role of MSI-2 proteins has been extensively studied and some target therapies proposed, no results regarding the role of MSI-2 in OSCC are reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its role seems to be explicated in different processes, among which: epithelial-mesenchymal transition, migration, invasion, cell proliferation, and drug resistance [17]. While for many tumors, such as those arising from breast [18], cervical [9], colon [19], lung [6], etc. the role of MSI-2 proteins has been extensively studied and some target therapies proposed, no results regarding the role of MSI-2 in OSCC are reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In bladder cancer, the differentiation antagonizing non-protein noding RNA (DANCR) long non-coding RNA (lncRNA) acts by sponging miR-149 increasing the expression of MSI2, getting worse a malignant phenotype [7]. In addition, MSI2 seems to be involved in patients' prognosis, resulting as prognostic factor in gastric [8] and cervical cancer [9]; in lung cancer, MSI2 emerged as a novel therapeutic target [10]. Several other factors that are responsible of the regulation of cell proliferation and cell cycle control have been proposed as diagnostic, prognostic, and therapeutic markers for certain malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging evidence suggests that MSI2 is an important factor in the development of cancers. 35 Wang et al have presented that MSI2 is significantly expressed in HCC tissues, thus promoting the migration and invasion of HCC cells. 36 Kudinov et al have reported that overexpression of MSI2 accelerates metastasis in mouse non-small cell lung cancer (NSCLC) cells and human NSCLC tumors.…”
mentioning
confidence: 99%
“…High expression of MSI2 mRNA is associated with decreased survival in acute myeloid leukaemia [49]. Furthermore, MSI2 may act as a prognostic biomarker in patients with cervical cancer [50], bladder cancer [51] and oesophageal squamous cell carcinoma [52]. It was also found that its expression is upregulated in CRC, which makes it applicable as a prognostic marker gene for CRC.…”
Section: Discussionmentioning
confidence: 99%